A experiência religiosa em situações de perda: pedir e não receber - Campanini, João Roberto (2011)
The purpose of this dissertation consists in understanding the experience of religious people who, while suffering imminent loss, asked, through prayer, that the loss would not happen, but had not had their requests answered. To reach this goal, a qualitative phenomenological research was done, based on an interview and analysis both planned and developed according to the methodological proposals of phenomenology. Since the reported experience, it was sought to understand how the unanswered request affects the religious belief. The case studied allowed to show how the unanswered request may affect the way to live faith and the manner of new meanings was built. Also was found, the importance of spiritual leaders and psychologists to follow the people who go through similar situations